Manajemen Mutu Terpadu dalam Pendidikan: Sebuah Literature Review Sistematik terhadap Tren dan Kontribusi pada Kepuasan Stakeholder (2020–2025) - Siti Ismatus Zahro; Fermy Anggelia Putri; Muhammad Fathurrobbani; Mu’allimin Mu’allimin (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
The quality of education is an important issue that requires an integrated and sustainable management system. One approach that is widely used is Total Quality Management (TQM), which focuses not only on achieving academic standards, but also on the satisfaction of all education stakeholders. Although many studies have discussed IQM, a synthesis is still needed to see how IQM has been applied over the past five years and its contribution to customer satisfaction in education. Therefore, the research questions asked are: (1) how has IQM research in education developed from 2020 to 2025, and (2) to what extent has it contributed to customer satisfaction in education? This article uses a qualitative method based on a literature review (LR). The search process was conducted through the Google Scholar and Publish or Perish databases using the keywords “Integrated Quality Management in Education.” The search yielded 20 articles, which were filtered into 18 relevant articles and further analyzed into 5 main articles. The review results show three main themes: quality system planning and integration, quality culture-based managerial strategies, and quality assurance oriented towards stakeholder satisfaction. The conclusion confirms that IQM contributes significantly to improving quality and customer satisfaction in education. Further research is recommended to test the empirical relationship between IQM practices and stakeholder satisfaction at various levels of education.